(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2025)
This comprehensive review explores the evolution from dynamic capabilities to dynamic green capabilities (GDCs) in the context of sustainable business practices. It examines the theoretical foundations, drivers, and challenges in developing GDCs across various industries. The study highlights the critical role of GDCs in enabling firms to sense, seize, and reconfigure resources to address environmental challenges while maintaining competitiveness. Key findings reveal that GDCs are driven by factors such as environmental regulations, market pressures, and strategic orientation, necessitating a proactive approach to sustainability. The review identifies organizational barriers and implementation issues as significant challenges in operationalizing GDCs, particularly for SMEs. It emphasizes the importance of open innovation and ecosystem interactions in fostering sustainable solutions. The paper concludes by discussing theoretical and practical implications, including the need for integrating sustainability into core business strategies and developing standardized frameworks for measuring progress. Future research directions are proposed, focusing on contextual variations, micro foundations, and the integration of digital technologies in GDC development.